2018
DOI: 10.1002/ab.21762
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of physical and relational victimization in children with ADHD: The role of social problems and aggression

Abstract: The social risk factors for physical and relational peer victimization were examined within a mixed-gender sample of children with and without attention-deficit/hyperactivity disorder (ADHD). Participants were 124 children (ages 8-12 years; 48% boys), with 47% exhibiting sub-clinical or clinical elevations in ADHD symptoms. ADHD and oppositional defiant disorder (ODD) symptom counts were assessed based on parent- and teacher-reports; parents rated children's social problems and teachers rated children's use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The present study showed that physical victimization and peer rejection predicted increases in later ADHD and irritability symptoms. ADHD symptoms were also cross-sectionally linked with peer rejection and physical victimization at Time 1 and Time 2, which is consistent with previous research demonstrating that higher symptoms of ADHD are crosssectionally associated with peer victimization (Fite, Evans, Cooley, & Rubens, 2014;McQuade, Breslend, & Groff, 2018) and rejection (Grygiel et al, 2018;Lee et al, 2018;McDonald & Gibson, 2017). Previous longitudinal studies have similarly demonstrated that negative peer interactions worsen ADHD or irritability symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed that physical victimization and peer rejection predicted increases in later ADHD and irritability symptoms. ADHD symptoms were also cross-sectionally linked with peer rejection and physical victimization at Time 1 and Time 2, which is consistent with previous research demonstrating that higher symptoms of ADHD are crosssectionally associated with peer victimization (Fite, Evans, Cooley, & Rubens, 2014;McQuade, Breslend, & Groff, 2018) and rejection (Grygiel et al, 2018;Lee et al, 2018;McDonald & Gibson, 2017). Previous longitudinal studies have similarly demonstrated that negative peer interactions worsen ADHD or irritability symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Children with ADHD are more likely than their peers to exhibit impulsive social behaviours (Gardner & Gerdes, 2015 ). Other children could hold negative attributions about children with ADHD and respond with rejection or victimisation (McQuade et al., 2018 ), isolating children with ADHD from their peers. We also found that increasing childhood social isolation was associated with age‐18 ADHD symptoms, over and above prior symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The YSR social problem subscale contains 11 items related to several areas of social functioning, including peer rejection (e.g., “I am not liked by other kids,” “I don't get along with other kids”), social interaction style (e.g., “I'm too dependent on adults,” “I would rather be with younger kids than kids my own age”), the impact of peer rejection (e.g., “I feel lonely”), and behaviors that are associated with peer rejection (e.g., “I am poorly coordinated or clumsy,” “I have a speech problem”). Scores on this subscale are significantly related to cross-informant (i.e., parent or teacher) ratings of these behaviors (Achenbach & Rescorla, 2001) and to other indices of social maladjustment (i.e., peer victimization; McQuade, Breslend, & Groff, 2017; Schwartz, 1999). Mean T scores averaged across participants in FGCB and WI groups on the social problem subscale was 57.7 at baseline, indicating elevated risk.…”
Section: Methodsmentioning
confidence: 99%